The Influence of Website Social Presence, Buyer Social Presence, Seller Social Presence, and Telepresence on Purchase Intention Through Trust and Enjoyment Among Airbnb Customers in Jakarta - Angelia Allice Penina Laura Kadir; Victor Soeindra (International Journal of Economics Accounting and Management, 2026)
The accelerated evolution of internet and mobile technologies has rendered digital interaction fundamental to contemporary daily life, particularly in supporting communication, learning, information access, entertainment, and commercial activities. This study examines the influence of website social presence, buyer social presence, and seller social presence on purchase intention, with trust and enjoyment serving as mediating variables, among Airbnb consumers in Jakarta. Using a sample of 130 respondents, data were analyzed through Structural Equation Modeling (SEM) employing AMOS 20.0. The empirical findings indicate that Social Presence of Website, Social Presence of Buyers, Social Presence of Sellers, Telepresence, Trust, and Enjoyment exert significant effects on purchase intention within the context of Airbnb’s peer-to-peer accommodation platform in Jakarta. Keywords: Social presence of website, social presence of buyers, social presence of sellers, trust, enjoyment, purchase intention, peer-to-peer accommodation, Airbnb.